Nanomedicine for cancer diagnosis and therapy: advancement, success and structure–activity relationship. (November 2017) - Bhise, Ketki; Sau, Samaresh; Alsaab, Hashem; Kashaw, Sushil Kumar; Tekade, Rakesh Kumar; Iyer, Arun K
Multifunctional nanoparticles (NPs), composed of organic and inorganic materials, have been explored as promising drug-delivery vehicles for cancer diagnosis and therapy. The success of nanosystems has been attributed to its smaller size, biocompatibility, selective tumor accumulation and reduced toxicity. The relationship among numbers of molecules in payload, NP diameter and encapsulation efficacy have crucial role in clinical translation. Advancement of bioengineering, and systematic fine-tuning of functional components to NPs have diversified their optical and theranostic properties. In this review, we summarize wide varieties of NPs, such as ultrasmall polymer–lipid hybrid NPs, dendrimers, liposomes, quantum dots, carbon nanotubes, gold NPs and iron oxide NPs. We also discuss their tumor targetability, tissue penetration, pharmacokinetics, and therapeutic and diagnostic properties.